Current advances of tubulin inhibitors as dual acting small molecules for cancer therapy. Issue 4 (11th February 2019) - Arnst, Kinsie E; Banerjee, Souvik; Chen, Hao; Deng, Shanshan; Hwang, Dong‐Jin; Li, Wei; Miller, Duane D
Abstract: Microtubule (MT)‐targeting agents are highly successful drugs as chemotherapeutic agents, and this is attributed to their ability to target MT dynamics and interfere with critical cellular functions, including, mitosis, cell signaling, intracellular trafficking, and angiogenesis. Because MT dynamics vary in the different stages of the cell cycle, these drugs tend to be the most effective against mitotic cells. While this class of drug has proven to be effective against many cancer types, significant hurdles still exist and include overcoming aspects such as dose limited toxicities and the development of resistance. Newer generations of developed drugs attack these problems and alternative approaches such as the development of dual tubulin and kinase inhibitors are being investigated. This approach offers the potential to show increased efficacy and lower toxicities. This review covers different categories of MT‐targeting agents, recent advances in dual inhibitors, and current challenges for this drug target.